Dynamic engagement in second language computer-mediated collaborative writing tasks: Does communication mode matter? - Aubrey, Scott (Studies in Second Language Learning and Teaching, 2022)
This study takes a dynamic approach to investigating engagement, examining fluctuations in cognitive-affective variables at regular time intervals during online collaborative second language (L2) writing tasks. Using online conference software and online editing software, 16 university students who use English as an L2, completed two collaborative problem-solution L2 writing tasks in two communication modes: video-chat and text-chat. After each task, learners viewed videos of their performances in 12 three-minute segments and were asked to rate their engagement on two scales (interest, focus). They were then interviewed about their attributions for fluctuations in their ratings. Group-level analysis revealed that learners experienced significantly higher focus and interest during tasks performed in video-chat mode than text-chat mode. This was contrasted with an analysis from a dynamic perspective, which produced a more nuanced picture of individual engagement trajectories during the tasks. Dynamic patterns of engagement fell into either moderately steady, increasing, decreasing, or rollercoaster pattern categories. A content analysis of 32 interviews revealed four factors that accounted for changes in engagement during tasks: task design (e.g., task familiarity), task process (e.g., instances of collaboration), task condition (e.g., communication mode), and learner factors (e.g., perceptions of proficiency).